2006
DOI: 10.1038/modpathol.3800582
|View full text |Cite
|
Sign up to set email alerts
|

Potential crosstalk between insulin-like growth factor receptor type 1 and epidermal growth factor receptor in progression and metastasis of pancreatic cancer

Abstract: The insulin-like growth factor receptor type 1 (IGF1R) and epidermal growth factor receptor (EGFR) are reportedly overexpressed in pancreatic cancer. However, the correlation between activated EGFR and IGF1R and their clinicopathological implications still remain unclear. The cellular localization and overexpression of IGF1R and EGFR were investigated immunohistochemically in primary invasive ductal pancreatic carcinomas obtained from 74 patients who underwent radical surgical resection. We also compared the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 25 publications
1
36
1
Order By: Relevance
“…Indeed, IGF-IR expression was identified as a useful predictor of liver metastasis in several tumor types including colorectal carcinoma (Oshima et al, 2008), uveal melanoma (All-Ericsson et al, 2002), gastrinoma (Furukawa et al, 2005) and pancreatic cancer (Ueda et al, 2006). Although numerous reports, including our own, have attributed the prometastatic effect of IGF-IR to its role in the regulation of matrix metalloproteinases, cell migration and invasion and cell survival (Samani et al, 2007), our present findings, to our knowledge, are the first to link the prometastatic function of IGF-IR to it ability to regulate the ECM composition and, in particular, type IV collagen expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IGF-IR expression was identified as a useful predictor of liver metastasis in several tumor types including colorectal carcinoma (Oshima et al, 2008), uveal melanoma (All-Ericsson et al, 2002), gastrinoma (Furukawa et al, 2005) and pancreatic cancer (Ueda et al, 2006). Although numerous reports, including our own, have attributed the prometastatic effect of IGF-IR to its role in the regulation of matrix metalloproteinases, cell migration and invasion and cell survival (Samani et al, 2007), our present findings, to our knowledge, are the first to link the prometastatic function of IGF-IR to it ability to regulate the ECM composition and, in particular, type IV collagen expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, a frequent overexpression of IGF-IR and its ligands has been reported [28,29]. IGF-IR can potently contribute not only to the development of tumors but also to the resistance to therapy [30,31]. In this sense, it has been recently reported that concomitant expression of MMP7 and activation of p-IGF-1R correlates with poor prognosis in colon cancer patients treated with inhibitors of EGFR [32].…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, in advanced pancreatic cancer, EGFR expression tends to increase, while IGF1R expression decreases. 26 Other studies have described IGF1R-mediated activation of EGFR through induction of an autocrine TGFa loop. 27,28 Unexpectedly, in the current study, mRNA levels of TGFa were decreased, while those of IGF1R increased.…”
Section: Discussionmentioning
confidence: 99%